Isolation of biologically active and morphologically intact exosomes from plasma of patients with cancer - Hong, Chang-Sook (J Extracell Vesicles, 2016)
OBJECTIVE: Isolation from human plasma of exosomes that retain functional and morphological integrity for probing their protein, lipid and nucleic acid content is a priority for the future use of exosomes as biomarkers. A method that meets these criteria and can be scaled up for patient monitoring is thus desirable. METHODS: Plasma specimens (1 mL) of patients with acute myeloid leukaemia (AML) or a head and neck squamous cell carcinoma (HNSCC) were differentially centrifuged, ultrafiltered and fractionated by size exclusion chromatography in small disposable columns (mini-SEC). Exosomes were eluted in phosphate-buffered saline and were evaluated by qNano for particle size and counts, morphology by transmission electron microscopy, protein content, molecular profiles by western blots, and for ability to modify functions of immune cells. RESULTS: Exosomes eluting in fractions #3–5 had a diameter ranging from 50 to 200 nm by qNano, with the fraction #4 containing the bulk of clean, unaggregated exosomes. The exosome elution profiles remained constant for repeated runs of the same plasma. Larger plasma volumes could be fractionated running multiple mini-SEC columns in parallel. Particle concentrations per millilitre of plasma in #4 fractions of AML and HNSCC were comparable and were higher (p<0.003) than those in normal controls. Isolated AML exosomes co-incubated with normal human NK cells inhibited NKG2D expression levels (p<0.004), and HNSCC exosomes suppressed activation (p<0.01) and proliferation of activated T lymphocytes (p<0.03). CONCLUSIONS: Mini-SEC allows for simple and reproducible isolation from human plasma of exosomes retaining structural integrity and functional activity. It enables molecular/functional analysis of the exosome content in serial specimens of human plasma for clinical applications.